The first description of the female of Tritonaclia kefersteinii (Butler, 1882)(Lepidoptera: Erebidae: Arctiinae: Syntomini), the type species of its genus - Przybyłowicz, Łukasz; Wiorek, Marcin (Zootaxa, 2023)
The previously unknown female of Tritonaclia kefersteinii (Butler, 1882), the type species of the genus Tritonaclia Hamspon, 1898 is described for the first time, based on a specimen from Marojejy National Park (North-east Madagascar). The female genitalia are described in detail and illustrated. The taxonomic affiliation of the newly discovered female and its conspecificity with the male are confirmed by both morphological and molecular characters. For the first time, clear diagnostic characters of the male genitalia are also provided and illustrated. Comments on the known distribution of the species are provided. The new findings allow the genus to be properly characterized as a contribution to the taxonomy of Madagascar Syntomini.